VISUM ET REPERTUM SEBAGAI ALAT BUKTI SURAT DALAM PRAKTEK PEMBUKTIAN PEMBUNUHAN BERENCANA (Studi Kasus Putusan Nomor 324/Pid.B/2020/PN Jkt.Tim. dan Putusan Nomor 1001/Pid.B/2021/PN Jkt.Tim.) - Triyana, Heri (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2023)
Premeditated murder is regulated in Article 340 of the Criminal Code which reads "Anyone who deliberately and premeditatedly kills another person is punished for the guilt of premeditated murder, with the death penalty or life imprisonment or temporary imprisonment for a maximum of twenty years". The approach method used in this study is the Qualitative Analysis Method. The results of this study indicate that the application of the law to the crime of premeditated murder and its legal consequences in the case of Decision Number 324/Pid.Sus/2020/PN.Jkt.Tim. and Decision Number 1001/Pid.B/2021/ PN.Jkt.Tim., each of the defendants has been proven legally and convincingly guilty of committing the crime of premeditated murder, and proven to have committed the crime of premeditated murder as stipulated in the indictment.